2003
DOI: 10.1002/eji.200323612
|View full text |Cite
|
Sign up to set email alerts
|

Human cytomegalovirus impairs dendritic cell function: a novel mechanism of human cytomegalovirus immune escape

Abstract: Human cytomegalovirus (HCMV) employs multiple mechanisms to evade the immune system and succeeds to persist lifelong in the host. Human dendritic cells (DC) are the main antigen-presenting cells and play the key role in inducing and maintaining immune responses. Here, we studied the interaction of HCMV with DC. We found that DC, irrespectively of their stage of maturation, were fully permissive for HCMV when endothelial celladapted HCMV strains were applied. When fibroblast-adapted strains were used, viral rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
100
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(106 citation statements)
references
References 36 publications
4
100
1
Order By: Relevance
“…This observation clearly suggests that a simple cellular receptor-mediated interaction with SARS-CoV is not by itself sufficient to activate DC. It has been reported that the ability to alter DC function by two large DNA viruses, HSV type 1 and human CMV, was mediated through soluble factors induced by immediate early and early gene products of viruses and was independent of a complete viral replication cycle (35,36). Whether certain SARS-CoV-encoded signals were required for the manipulation of DC function is currently under investigation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This observation clearly suggests that a simple cellular receptor-mediated interaction with SARS-CoV is not by itself sufficient to activate DC. It has been reported that the ability to alter DC function by two large DNA viruses, HSV type 1 and human CMV, was mediated through soluble factors induced by immediate early and early gene products of viruses and was independent of a complete viral replication cycle (35,36). Whether certain SARS-CoV-encoded signals were required for the manipulation of DC function is currently under investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, the ability to alter the function of host cells by some viruses appears to be independent of viral replication (35,36). Therefore, we designed a series of experiments, as described below, aimed to determine whether SARS-CoV could have any impact on the function of M and DC.…”
Section: Sars-cov Does Not Add To the Cell Death Of Cultured M And Dcmentioning
confidence: 99%
“…In another study, a similar observation is reported in case of HCMV where signal delivery required for T cell activation is impaired in infected DCs which lead to persistent viral infection in the host system. In addition, HCMV infection diminishes the expression of adhesion molecules which in turn may lead to inefficient DC migration [11]. HCV induces immunosuppression in DCs during maturation.…”
Section: Dendritic Cell (Dc) Response During Viral Infectionmentioning
confidence: 99%
“…Since infected DCs could be paralysed [4] and made unable to ensure activation of In an in vitro model where HCMV-infected Wbroblasts were co-cultured with monocyte-derived dendritic cells, we demonstrated that immature DCs (iDC) acquired a mature phenotype (mDC), as assessed by an up-regulation of CD80, CD86 and CD83 expression on the cell surface and by the secretion of huge amounts of TNF- [24,25]. We further demonstrated that HCMV-infected Wbroblasts were sensitive to apoptosis mediated by TNF-, but only within the Wrst hours after addition of the virus.…”
Section: Role Of Cross-presentation To Bypass Viral Subversion and Inmentioning
confidence: 99%
“…Moreover, some viruses such as HIV and human cytomegalovirus (HCMV) use the C-type lectin receptor DC-SIGN on dendritic cells as a vector to ensure their transmission to other cells either in the periphery or in lymph nodes [1,2]. Direct arguments that DCs are real targets for HCMV in vivo are suggested, for instance, by the ability of the virus to infect hematopoietic progenitor cells [3] and by the presence of viral DNA in puriWed DCs from viremic renal transplant patients as well as from healthy virus carriers [4,5]. HCMV is a latent herpesvirus, which can be considered as a spearhead in exploiting co-existence with the host to develop numerous immunoevasion mechanisms, and virus-encoded immunoevasins have been described that impair many of dendritic cells functions including antigen presentation to CD4+ and CD8+ T cells [6].…”
Section: Introductionmentioning
confidence: 99%